International Consensus Statement on the Use of Uterotonic Agents During Cesarean Section. Issue 3 (September 2020) - Heesen, M.; Carvalho, B.; Carvalho, J.C.A.; Duvekot, J.J.; Dyer, R.A.; Lucas, D.N.; McDonnell, N.; Orbach-Zinger, S.; Kinsella, S.M.
Abstract : ( Anaesthesia . 2019;74:1305–1319) Uterotonics are routinely used after delivery to manage uterine tone. While various guidelines exist for general management during cesarean deliveries, management of uterine tone following vaginal delivery, and treatment of postpartum hemorrhage, no previous international guideline has addressed uterotonic management during and following cesarean section. The use of uterotonics is largely based on tradition and varies in the choice of drug, timing of administration, dose, route, and speed, and maintenance of administration. Both first-line (oxytocin, carbetocin) and second-line uterotonics carry risk for adverse effects such as hypotension, tachycardia, and ST-segment depression. This consensus statement provides 10 recommendations for the use of uterotonic agents during cesarean section.